A Case of Langerhans Cell Histocytosis Masquerading as a Colon Polyp. (11th September 2019) - Bishop, Bradie; Lynch, David; Brady, Robert
Abstract: Langerhans cell histocytosis, otherwise known as eosinophilic granuloma, is a rare neoplastic process composed of Langerhans cells and eosinophils. Most cases present during childhood, with the bones and skin being the most common organs involved. Other organs are occasionally involved, with some systemic cases involving the gastrointestinal tract. Presentations of Langerhans cell histocytosis range from single-organ involvement to systemic involvement. Fewer than five cases of isolated Langerhans cell histocytosis in the gastrointestinal system in adults have been reported. We present a case of Langerhans cell histocytosis incidentally discovered during routine colonoscopy in a 67-year-old otherwise healthy woman. Initial colonoscopy performed 7 years prior demonstrated a sessile serrated adenoma, fragments of tubular adenomas, and hyperplastic polyps. Repeat colonoscopy 3 years later demonstrated a sessile serrated adenoma and hyperplastic polyp. Upon repeat colonoscopy 4 years later, the patient had nine subcentimeter polyps. One of the ascending colon polyp fragments demonstrated a well-circumscribed, submucosal nodule of granular pink histocytes with folded to clefted and reniform nuclei. Numerous eosinophils were present in the background. These findings were consistent with Langerhans cell histocytosis. The remaining polyps were a tubular adenoma and hyperplastic polyps. A CT chest/abdomen/pelvis did not demonstrate any evidence of systemic disease. One year postdiagnosis, the patient had not had recurrence of symptoms. Unifocal Langerhans cell histocytosis rarely presents in the gastrointestinal tract of an adult and is believed to have a good prognosis with limited recurrence. The patient is being closely followed for development of systemic disease.